Evaluation of muscle damage, body temperature, peak torque and fatigue index in three different methods of strength gain - Barros, N. A.; Aidar, F. J.; de Matos, D. P.; de Souza, R. F.; Neves, E. B.; Cabral, B. G. A. T.; Camargo, E. A.; Reis, V. M. (International Journal of Exercise Science, 2020)
The aim of this study was to evaluate and compare three different strength training protocols for the lower limbs by using biochemical indicators of muscle damage, thermographic analysis, and neuromuscular performance. In total, 10 men (age: 22.50 ± 2.84 years; weight, 75.45 ± 6.86 kg) completed the study. All the athletes were subjected to three methods of resistance training (RT): traditional, tension, and occlusion training. Serum concentrations of creatine kinase, lactate dehydrogenase, aspartate aminotransferase, and alanine aminotransferase were used as indicators of muscle damage. To measure muscle strength, the peak force, and fatigue index were determined using a Kratos load cell. Images were captured using an infrared camera (FLIR T640sc). The vascular occlusion method demonstrated a 33% reduction in post-training peak torque (p < 0.001; ?2p: 2.74), which was recovered within 24 h (p < 0.001; ?2p: 1.08). The thermographic analysis revealed a reduction in skin temperature in both thighs after the tension (-9.37%) and vascular occlusion (-6.01%) methods. In conclusion, the occlusion training seems to provide additional benefits as compared to the other two methods of strength training.